Presidential coattails in coalitional presidentialism. (March 2019) - Borges, André; Turgeon, Mathieu
Research on presidential coattails in elections has focused nearly exclusively on two-party systems like the United States. Much less is known, however, about presidential coattails in multiparty systems where electoral and governing coalitions are common currency. Under coalitional presidentialism, we argue that presidential coattails are diffused, benefiting the president's party but also her coalition party members, especially those most strongly associated with the coalition itself. Using electoral data from Chile and Brazil, two widely studied but distinct cases of coalitional presidentialism, we find strong evidence supporting this claim. The results carry important implications for students of coalitional presidentialism, presidential coattails, and party systems, more generally.